Double-tapered conical taper in primary and revision surgery: rationale and short-term follow-up. (November 2018) - Perticarini, Loris; Mosconi, Mario; Medetti, Marta; Caliogna, Laura; Benazzo, Francesco M
Background: The new double-conical tapered stem is a novel cementless modular system, which is indicated for both primary and revision surgeries. It has been designed with different angles at the proximal (5°) and distal sections (1° 36') in order to obtain optimal fixation by proximal and distal fit and fill of the femoral canal. Aim: The aim of this prospective study was to evaluate the short-term clinical and radiographic outcomes of primary and revision hip surgery with the new double-conical stem. Methods: 61 stems were implanted (December 2013 to September 2016) in 42 cases of primary and in 19 cases of revision surgery. The mean age of patients was 64.7 (17–94; standard deviation [SD] 21.9) years. Results: The mean body mass index of the patients was 24.6 (17–34.6). In 3 cases of developmental dysplasia of the hip we performed femoral shortening osteotomy. The mean follow-up was 26 (8–40) months. 3 patients died due to causes unrelated to surgery. Postoperative complications included 3 hip dislocations, 2 infections and 1 case of stem explant for metastatic tumour. For all other cases, at the last follow-up radiographs showed no loosening, no radiolucent lines nor subsidence. The mean Harris Hip Score significantly improved from 45 (range 35–58) preoperatively to 87 (range 75–94). Leg length discrepancy was found in 10% of cases but never >1 cm. Conclusions: Radiographic analysis showed the bone-stem contact full at 2 levels of taper. The double-tapered prosthetic stem can therefore be usefully employed both in primary and in revision surgeries.